Evaluation of Urban Green Open Space Asset Utilisation : (Study of Tourism Perception and Preference in Bandung City Parks) - Andrianto, Tomy; Tiafahmi Angestiwi; Aceng Gima Sugiama (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2023)
Urban Green Open Space/Ruang Terbuka Hijau Kawasan Perkotaan (RTHKP) is an essential part of the urban population ecosystem, one of which is the City of Bandung. One of the uses of RTHKP is as a city park, an alternative for tourist activities. This study aims to evaluate the use of City Parks as one of the RTHKP assets by understanding the perceptions and activity preferences of residents of Greater Bandung (Bandung City, Bandung Regency, West Bandung Regency, Cimahi) related to city parks in Bandung City. This research uses quantitative methods with descriptive analysis to understand perceptions and preferences as well as regression and correlation analysis to understand the relationship between the two variables. Two hundred sixty-five resident respondents who have visited one of the eleven city parks in Bandung City have completed the questionnaire. The result is that the City Park aspect in Bandung City can be a place for recreation and a children's playground that gets the highest score for perceptions and willingness to use public transportation, and the safety aspect still needs to be considered. Meanwhile, for activity preferences in city parks in Bandung City, the highest position is a place for refreshing, recreation and sports, and the lowest is for socialising and inviting children to play. There is a significant relationship between the perceptions and preferences of residents of Greater Bandung, especially for recreational and refreshing activities.